1998
DOI: 10.1021/es970566w
|View full text |Cite
|
Sign up to set email alerts
|

On-Road Emissions of Particulate Polycyclic Aromatic Hydrocarbons and Black Carbon from Gasoline and Diesel Vehicles

Abstract: Motor vehicles are a significant source of fine carbonaceous particle emissions. Fuels have been reformulated and vehicle technologies have advanced, so an updated assessment of vehicular emissions is needed. Gas- and particle-phase pollutant concentrations were measured in the Caldecott Tunnel in the San Francisco Bay Area during the summer of 1996. Separate samples were collected for uphill traffic in two tunnel bores:  one bore was influenced by heavy-duty diesel truck emissions; a second bore was reserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
252
5
10

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 498 publications
(291 citation statements)
references
References 23 publications
24
252
5
10
Order By: Relevance
“…Other reported mean BC EFs tend to be for a somewhat lower count based HDDV fraction (<1%). 14,15,34 Results from that work fall well below even our median values of Figure 4.…”
Section: Resultsmentioning
confidence: 44%
“…Other reported mean BC EFs tend to be for a somewhat lower count based HDDV fraction (<1%). 14,15,34 Results from that work fall well below even our median values of Figure 4.…”
Section: Resultsmentioning
confidence: 44%
“…Source diagnostics based on several PAH isomeric ratios (Supplementary material) indicated that indoor particulate PAHs were mainly derived from fossil fuel combustion such as automobile exhaust. However, other studies indicated that particulate PAHs newly discharged from automobiles were mainly distributed in the ultrafine fraction (Miguel et al, 1998;Phuleria et al, 2006). A similar inconsistency was also observed in Saitama City of Japan, which was ascribed to coagulation of fine particles (Kawanaka et al, 2009).…”
Section: Occurrence and Particle Size Distribution Of Pahsmentioning
confidence: 74%
“…A number of articles and reports have been published regarding the contribution of traffic to OC and EC in Europe and the USA (Kerminen et al, 1997;Miguel et al, 1998;Fraser et al, 1999;Moosmüller et al, 2000;Shi et al, 2000;Kohler et al, 2001;Ruellan et al, 2001). …”
Section: Introductionmentioning
confidence: 99%